Changes in Semolina Yellow Pigment Content and Carotenoid Composition During Pasta Processing. Issue 6 (30th June 2015) - Chiremba, Constance; Pozniak, Curtis J.; Fu, Bin Xiao
Abstract : Changes in total yellow pigment (TYP) content and carotenoid composition were examined at different stages of pasta processing. Semolina samples were milled from durum genotypes with and without the Lpx‐B1.1 gene deletion and then processed into dry pasta. Significant pigment loss (12.8–15.3%) based on TYP content was observed from semolina to dough in genotypes without the gene deletion. Such loss remained low (2.0–2.8%) for genotypes with the Lpx‐B1.1 gene deletion. Extrusion and drying processes did not result in substantial pigment loss. The overall pigment loss (from semolina to dried pasta) of genotypes with the gene deletion was 9.1–12.8%, in comparison with 19.0–21.7% in genotypes without the deletion. Changes in carotenoids examined by ultra‐performance liquid chromatography showed that lutein decreased gradually from representing 80% of total carotenoids to 70% of total carotenoids during pasta processing. The reduction of lutein was mostly during dough mixing, with a decrease of 16.7% in genotypes with the Lpx‐B1.1 deletion and 27.8% in genotypes without the deletion. Minor carotenoids increased during pasta drying, possibly at the expense of lutein. Results of this study showed that although breeding for elevated yellow pigments is the key, pasta color can be further improved by reducing pigment losses at different stages of pasta processing through selection of genotypes with Lpx‐B1.1 deletion and applying a vacuum during mixing and extrusion processes.